The World Trade Organization : law, practice, and policy - Matsushita, Mitsuo (O.U.P. OxfordGB, 2003)
Provides a comprehensive overview of the law and practice of the WTO. Begins with the institutional law of the WTO (such as the sources of law and remedies of the dispute settlement system), and then tackles the principle substantive obligations of the WTO regime. Considers unfair trade, regional trading arrangements, and developing countries. Deals with the consequences of globalization: firstly where WTO law confronts legal regimes governing issues of competition and intellectual property; and, secondly, where free trade is seen to be incompatible with certain human rights.